Management of science and technology information projects supported by IDRC (IDRC OttawaCA, 1989)
Presents guidelines for managing IDRC-funded projects. Covers topics such as the project management process; the project manager; project planning; project sustainability; project evaluation; financial administration; IDRC library and training.
Report of a meeting of Science and Technology Information Project Managers held in Addis Abba, Ethiopia, November 21-25, 1988. Bibliography: p.vi-viii